Altered Functional Hubs and Connectivity in Type 2 Diabetes Mellitus Without Mild Cognitive Impairment - Li, Yifan; Liang, Yi; Tan, Xin; Chen, Yuna; Yang, Jinquan; Zeng, Hui; Qin, Chunhong; Feng, Yue; Ma, Xiaomeng; Qiu, Shijun (Frontiers in Neurology, 2020)
Type 2 diabetes mellitus (T2DM) related cognitive declines are associated with neuroimaging changes in the brain. However, only a few studies have focused on early functional changes in T2DM prior to mild cognitive impairment (MCI). In this study, degree centrality (DC) was used to evaluate the functional changes of the whole brain in T2DM without MCI. Compared with healthy controls (HCs), T2DM subjects showed increased DC in the right cerebellum lobule III-V. Furthermore, seed-based functional connectivity (FC) analysis found that right cerebellum lobule III-V of T2DM subjects had increased FC with right cerebellum crus II and lobule VI, right temporal inferior/ middle gyrus, plus right hippocampus. These may indicate an important pathophysiological mechanism for compensation in T2DM without MCI.